Does Raising Environmental Awareness and Creating Pro-Environmental Attitudes Drive the Intention to Revisit Among Visitors? - Ari Prabowo; Etty Sri Wahyuni; Surya Bakti; Pipit Buana Sari; Yossie Rossanty (Budapest International Research and Critics University, 2022)
This research aims to investigate and analyze the impact of creative economy actors' blue ocean strategy on the intention of visitors to return to the Bukit Lawang area of North Sumatera. This study employs quantitatively oriented, associative research. This study's population consisted only of local visitors who traveled to Bukit Lawang, North Sumatera, and whose actual amount could not be determined. The sampling methodology used a nonprobability sampling method with a purposive sample method, in which the researchers obtain data from the most comprehensive and diverse sources in order to satisfy varied informational objectives. The sample criteria consist of local visitors who have visited Bukit Lawang more than once, and the lameshow algorithm ensures that there are 100 study samples. The methods of data collection include surveys and interviews. Multiple linear regression analysis is used as the technique of data analysis. The partial effect of raising environmental awareness and creating pro-environmental attitudes were shown have an influence on the intention to revisit among visitors in the Bukit Lawang area of North Sumatera. This study demonstrates that simultaneously, there is an effect of raises awareness among visitors and creates pro-environmental attitudes among those who intend return to the Bukit Lawang area. The coefficient of determination test yielded an adjusted R square value of 0.702% (70.2 percent). This demonstrates that the raise awareness and create pro-environmental attitudes factors may explain 70.2% of the revisit intention, the remaining 29.8% is impacted by variables not explored in this study.